Low Extracellular pH Induces Damage in the Pancreatic Acinar Cell by Enhancing Calcium Signaling - Reed, Anamika M. (American Society for Biochemistry and Molecular Biology, 2011)
Low extracellular pH (pHe) occurs in a number of clinical conditions and sensitizes to the development of pancreatitis. The mechanisms responsible for this sensitization are unknown. Because abnormal Ca(2+) signaling underlies many of the early steps in the pathogenesis of pancreatitis, we evaluated the effect of decreasing pHe from 7.4 to 7.0 on Ca(2+) signals in the acinar cell. Low pHe significantly increased the amplitude of cerulein-induced Ca(2+) signals. The enhancement in amplitude was localized to the basolateral region of the acinar cell and was reduced by pretreatment with ryanodine receptor (RYR) inhibitors. Because basolateral RYRs also have been implicated in the pathogenesis of pancreatitis, we evaluated the effects of RYR inhibitors on pancreatitis responses in acidic conditions. RYR inhibitors significantly reduced the sensitizing effects of low pHe on zymogen activation and cellular injury. These findings suggest that enhanced RYR-mediated Ca(2+) signaling in the basolateral region of the acinar cell is responsible for the injurious effects of low pHe on the exocrine pancreas.